2021
DOI: 10.1111/jon.12834
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Resting‐State Functional Brain Connectivity and Correlations with Vestibular/Ocular‐Motor Screening Measures in Postconcussion Vestibular Dysfunction

Abstract: BACKGROUND AND PURPOSE: Vestibular symptoms after concussion are common and associated with protracted recovery. The purpose of this study is to define resting-state functional MRI (rs-fMRI) brain connectivity alterations in patients with postconcussion vestibular dysfunction (PCVD) and correlations between rs-fMRI connectivity and symptoms provoked during Vestibular/Ocular-Motor Screening (VOMS) assessment. METHODS: Prospective IRB approved study. Study group: 12 subjects with subacute PCVD (2-10 weeks); cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Consistent with literature showing global hyper-connectivity patterns between brain networks (Churchill et al, 2017(Churchill et al, , 2019Manning, 2017) as well as previous findings specific to the motor network post-concussion (Schmidt et al, 2018;Trofimova et al, 2021), adolescents clinically recovered from concussion showed increased functional DMN-left lateral premotor cortex connectivity compared to controls. Regardless of the covariates included, there were cluster-level group differences in connectivity between DMN and right and left lateral premotor regions, suggesting that this is an important region bilaterally.…”
Section: Dan-motor Functional Connectivitysupporting
confidence: 91%
“…Consistent with literature showing global hyper-connectivity patterns between brain networks (Churchill et al, 2017(Churchill et al, , 2019Manning, 2017) as well as previous findings specific to the motor network post-concussion (Schmidt et al, 2018;Trofimova et al, 2021), adolescents clinically recovered from concussion showed increased functional DMN-left lateral premotor cortex connectivity compared to controls. Regardless of the covariates included, there were cluster-level group differences in connectivity between DMN and right and left lateral premotor regions, suggesting that this is an important region bilaterally.…”
Section: Dan-motor Functional Connectivitysupporting
confidence: 91%
“…There is considerable interest and ongoing effort to characterize the cortical network subserving vestibular function and recent clinical and neuroimaging studies evince complex interactions between central vestibular substrates and cognitive, oculomotor, and emotional/affective domains (Indovina et al, 2020; Raiser et al, 2020). Brain regions involved in visuospatial, affective, and integrative functions also subserve vestibular processing, modulate oculomotor gain and visual attention, and may contribute to dysfunction in a subset of syndromes including PPPD and PCVD (Allen et al, 2021; Passamonti et al, 2018; Riccelli et al, 2017; Trofimova et al, 2021). This study is, to our knowledge, the first to situate these ancillary connections in the larger context of vestibular function and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was recently reported that control participants and patients with subacute post‐concussive vestibular dysfunction (PCVD) exhibit differential recruitment of the visual, parieto‐insular, parietal, frontal, and cingulate cortices and hippocampus in response to visual‐vestibular provocation, and noted that activity in the frontal eye field, posterior hippocampus, and middle temporal visual area (hMST/V5) was associated with Vestibular Ocular Motor Screening (VOMS: Mucha et al, 2014) scores across all control and PCVD participants (Allen et al, 2021). Subjects with higher resting‐state connectivity between the posterior hippocampus and ipsilateral V5, and among the left and right‐hemisphere MSO, PIVC, and right anterior insula, have also been shown to exhibit increased symptoms during VOMS testing (Trofimova et al, 2021). These results not only implicate visuospatial and integrative areas in vestibular function and dysfunction, but also suggest that, in some cases, dysfunction may arise from an overreliance on visual cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parietal regions are involved in processing vestibular information for the perception of self-motion [111]. In cases of post-concussion or mTBI vestibular dysfunction, vestibular impairment causes a myriad of symptoms related to imbalance and disorientation, which often manifests as dizziness/vertigo and/or lightheadedness and may be accompanied by nausea as well [112,113]. For non-hospitalized TBI patients, vestibular function testing detects abnormalities in somewhere between about 30 to 60% of those tested and symptoms may continue for in excess of one year in 10 to 15% of patients with a mild concussion [10,[114][115][116][117].…”
Section: Vestibular Systemmentioning
confidence: 99%